Digitalisasi Laporan Keuangan sebagai Upaya Transparansi dan Akuntabilitas BUMDes Bebedahan Berkah - Asih Handayani; Anisa, Anisa; Effriyanti, Effriyanti; Faozi, Khanif (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
BUMDes Bebedahan Berkah is an enterprise owned by the village of West Kaduagung, Cibadak sub-district, Lebak district, Banten. BUMDes Bebedahan Berkah is in the sector of rental services for shophouses located near the West Kaduagung Village Office. The BUMDes financial management is still done manually using a cash book, resulting in the risk of recording errors, calculations, and potential misuse of funds. As a result, many receivables are uncollectible, business development is hampered, and decision-making is difficult due to the absence of comprehensive financial reports. This activity aims to improve the financial management skills of BUMDes through training and assistance in financial management and reporting using the TAKABUMDes application. This activity succeeded in improving the skills and abilities of BUMDes management in managing finances and making financial reports, so that transparency and accountability have been achieved. Long-term success requires consistent effort, sufficient funding support, and close cooperation between stakeholders to ensure the sustainability of BUMDES.